2018
DOI: 10.5114/jcb.2018.79335
|View full text |Cite
|
Sign up to set email alerts
|

Single fraction computed tomography-guided high-dose-rate brachytherapy or stereotactic body radiotherapy for primary and metastatic lung tumors?

Abstract: PurposeTo provide a pilot dosimetric study of computed tomography (CT)-guided high-dose-rate (HDR) brachytherapy (BRT) and stereotactic body radiotherapy (SBRT) for primary and metastatic lung lesions.Material and methodsFor nine lung primary and metastasis patients, 3D image-based BRT plan using a single virtual catheter was planned for 34 Gy in single fraction to the gross tumor volume (GTV) + 3 mm margin to account for tumor deformation. These plans were compared to margin-based (MB-) and robustness optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Following the law of inverse squared ratio, the dose profile of SABT formed super-high dose peak for GTVL, and the dose fell more rapidly outside the tumor target area compared to that with SBRT (Figure 3D, E), resulting in a higher dose in the tumor target and a lower dose in OARs. A recent study using virtual brachytherapy plan in a single fraction to GTVL indicated comparable dosimetric parameters between brachytherapy and SBRT [21]. Our data based on realistic brachytherapy plan showed that there were no statistically significant differences in the D95% for the lung tumor target between SABT and SBRT plans (all p > 0.05).…”
Section: Discussionsupporting
confidence: 44%
“…Following the law of inverse squared ratio, the dose profile of SABT formed super-high dose peak for GTVL, and the dose fell more rapidly outside the tumor target area compared to that with SBRT (Figure 3D, E), resulting in a higher dose in the tumor target and a lower dose in OARs. A recent study using virtual brachytherapy plan in a single fraction to GTVL indicated comparable dosimetric parameters between brachytherapy and SBRT [21]. Our data based on realistic brachytherapy plan showed that there were no statistically significant differences in the D95% for the lung tumor target between SABT and SBRT plans (all p > 0.05).…”
Section: Discussionsupporting
confidence: 44%
“…A plan comparison was conducted to virtual SBRT plans using the original HDR BT planning CT. In the available literature comparing both modalities, usually CT datasets acquired for SBRT were used and compared to virtual brachytherapy plans [ 26 , 27 ]. To the best of our knowledge only one other study by Hass et al has so far used original BT planning CT data and compared to virtual SBRT plans [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the other dosimetric parameters were not significant for OARs, but BT resulted in lower values for three out of five parameters. Chan et al [45] performed a dosimetric analysis between HDR-BT and SBRT for primary and metastatic lung lesions. Virtual BT plans were created for 9 patients treated with SBRT using a single catheter.…”
Section: Lungmentioning
confidence: 99%
“…As for BT, the TG-43 formalism was used in all but six studies. In four papers, no information on the method of dose calculation was provided and more advanced model-based dose calculation algorithms (MBDCA) were used only in two studies [45,63]. Chan et al [45] calculated BT dose distributions in the lung using the Advanced Collapsed Cone Engine (ACE; Elekta Brachytherapy, Veenendaal, the Netherlands).…”
Section: Dose Calculation Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation